Setbacks vs. extensions : case study of corner terraced houses in Taman Universiti, Johor Bahru [electronic resource] - Chee, Jun Yean, 1991-; Chau, Loon Wai; Foziah Johar (2015)
Project Paper (Sarjana Muda Perancangan dan Wilayah) - Universiti Teknologi Malaysia, 2015